2010
DOI: 10.1128/iai.00798-10
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Receptor CXCR2 Ligand KC (CXCL1) Mediates Neutrophil Recruitment and Is Critical for Development of Experimental Lyme Arthritis and Carditis

Abstract: Deletion of the chemokine receptor CXCR2 prevents the recruitment of neutrophils into tissues and subsequent development of experimental Lyme arthritis. Following footpad inoculation of Borrelia burgdorferi, the agent of Lyme disease, expression of the CXCR2 ligand KC (CXCL1) is highly upregulated in the joints of arthritis-susceptible mice and is likely to play an important role in the recruitment of neutrophils to the site of infection. To test this hypothesis, we infected C3H KC ؊/؊ mice with B. burgdorferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 56 publications
7
100
0
Order By: Relevance
“…IL-6, CXCL1 (KC), CXCL2 (MIP-2), CXCL9 (MIG), CXCL10 (IP-10), CCL2 (MCP-1), CCL3/4 (MIP-1␣/␤), and CCL5 (RANTES) cytokines/chemokines are essential for recruitment of several cell types (20,26). The proinflammatory cytokine IL-6 and the chemokines CXCL1 and CXCL2, which mainly induce neutrophil migration (27,28), were significantly overexpressed in PEs of NYVAC-C Δ3-injected mice compared to those of mice injected with the other deletion mutants (Fig. 3A to C).…”
Section: Resultsmentioning
confidence: 99%
“…IL-6, CXCL1 (KC), CXCL2 (MIP-2), CXCL9 (MIG), CXCL10 (IP-10), CCL2 (MCP-1), CCL3/4 (MIP-1␣/␤), and CCL5 (RANTES) cytokines/chemokines are essential for recruitment of several cell types (20,26). The proinflammatory cytokine IL-6 and the chemokines CXCL1 and CXCL2, which mainly induce neutrophil migration (27,28), were significantly overexpressed in PEs of NYVAC-C Δ3-injected mice compared to those of mice injected with the other deletion mutants (Fig. 3A to C).…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of neutrophil-and macrophage/monocyteattracting chemokines in the CRB and BS in LysMCre-SOCS3 fl//fl mice with atypical EAE CXCL1, CXCL2, and CCL2 are potent neutrophil and macrophage chemoattractants (8,37,38). Given the increased levels of neutrophils and macrophages/monocytes infiltrating into the CRB and BS in LysMCre-SOCS3 fl//fl mice with atypical EAE compared with SOCS3…”
Section: Neutrophil Infiltration Into the Crb And Bs Is Prominent Inmentioning
confidence: 99%
“…For example, the 2 commonly studied CXCR2 chemokine ligands in the mouse, CXCL1 (Gro alpha, KC), and CXCL2 (Gro beta, MIP-2) were shown to have differing affinities for the CXCR2 receptor, resulting in a hierarchy of neutrophil chemotaxis and activation (Lee et al 1995;Wuyts et al 1996). Furthermore, the kinetics of expression and tissue expression profiles in several different models of infection revealed that these CXCR2 ligands display both differences in temporal and spatial responses, suggesting differing functional roles for these ligands in different disease models (Rovai et al 1998;Ritzman et al 2010;Mei et al 2012).…”
Section: Introductionmentioning
confidence: 99%